The Impact of Unanticipated Output and Consumer Prices on Wilcat Strikes - Fisher, E.; Percy, M. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1983)
An empirical investigation of the impact of unanticipated changes in output and consumer prices, as well as other economic and sociological variables, on midcontract or wildcat strikes, with particular reference to British Columbia's copper industry.